2021
DOI: 10.3390/nu13010166
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Vitamin D and Dental Caries in 7-Year-Old Children in Porto Metropolitan Area

Abstract: Vitamin D deficiency has been associated with significant changes in dental structures. In children, it can induce enamel and dentin defects, which have been identified as risk factors for caries. This study aimed to assess the association between low serum 25-hydroxyvitamin D (25(OH) D) levels (<30 ng/mL) and the prevalence of caries in the permanent teeth and mixed dentition of 7-year-old children. A sample of 335 children from the population-based birth cohort Generation XXI (Porto, Portugal) was include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Enamel and dentin abnormalities have been considered in children as caries risk factors. As a result, optimum vitamin D3 levels in children are required as a secondary preventive intervention for dental cavities in the permanent dentition [ 26 ]. Another study concluded that among the vitamin D3 receptor polymorphisms studied, a relation was found between the FokI polymorphism (rs10735810) and the risk of dental caries, with the protective effect of the f allele and ff genotype [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enamel and dentin abnormalities have been considered in children as caries risk factors. As a result, optimum vitamin D3 levels in children are required as a secondary preventive intervention for dental cavities in the permanent dentition [ 26 ]. Another study concluded that among the vitamin D3 receptor polymorphisms studied, a relation was found between the FokI polymorphism (rs10735810) and the risk of dental caries, with the protective effect of the f allele and ff genotype [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between 25(OH)D and caries even extends beyond the primary dentition into the permanent dentition of children. A study of 7-year-olds in Portugal revealed that suboptimal 25(OH)D concentrations were significantly associated with advanced decay in permanent teeth [28]. A population-based prospective cohort study among mothers and children in the Netherlands reported that low maternal and neonatal 25(OH)D concentrations are associated with accelerated dental development of permanent teeth in children [29].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last several years, the literature on the association between 25(OH)D and children's oral health has grown [5,22,26,28,29,36]. One recent study reported that lower prenatal and neonatal concentrations of 25(OH)D were associated with an advanced dental age of children, suggesting that inadequate 25(OH)D accelerates dental development [29].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between nutrition, general health, and dental caries studies dates to the 1920s. The study by Mellanby and Pattison, published in 1928, provides the first evidence that vitamin D deficiency is associated with dental caries in children [7,8]. A growing body of studies and evidence shows that low serum concentrations of 25-hydroxyvitamin D (25(OH)D) are associated with increased caries experience [2,[8][9][10][11].…”
Section: Vitamin D Deficiency In Pediatric Dentistrymentioning
confidence: 99%